Bina Kesadaran Hak-hak Perempuan Dan Anak Dalam Lingkup Hukum Keluarga Islam Di Kampung Kandang Haur Desa Kadikaran Kecamatan Ciruas Kabupaten Serang - Hilman Taqiyudin; Hapizul Ahdi; M. Riza Pahlefi (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2022)
A good understanding of the substance and implementation of Islamic law in society can create a good religious and state life. The implementation of Islamic law that is very significant is the implementation of women's rights and children's rights both in terms of fiqh law and legislation as well as compilations where these rights need to be fulfilled. In order to fulfill the rights of women and children, it is necessary to raise awareness and understanding of the rights of women and children themselves in society in a comprehensive manner. This service activity focuses on raising awareness of women's and children's rights within the scope of Islamic family law in Kandang Haur, Kadikaran Village, Ciruas District, Serang Regency. The method used in this activity is Participatory Action Research (PAR) or the process of community empowerment through participation and social mobilization using a form of community-based research which is research to address problems experienced by the community. The purpose of this activity is to convey good information and awareness education to the public regarding the rights of women and children within the scope of Islamic family law so as to create harmonious family resilience as expected by Islamic teachings themselves. Keywords: Awareness, Women's Rights, Children's Rights, Islamic Family Law